The Demonstration of Gender Equality in Family Relationships - Kurbonova Dilnoza Takhirovna (International Journal on Integrated Education, 2022)
This paper focuses on the issue of women at the level of state policy, women's role in family, women's role in bringing up children, issues that are implemented in conditions of social protection of women and improvement of working conditions.